The cartographer's secret - Cooper, Tea (Harper Muse, 2021)
"A gripping historical mystery for fans of Kate Morton and Natasha Lester's The Paris Seamstress, The Cartographer's Secret follows a young woman's quest to heal a family rift as she becomes entangled in one of Australia's greatest historical puzzles"--